Geographical distribution of the geological formations of lapis lazuli and their role in the emergence of ancient trade routes with Mesopotamia in the fourth and third millennium BC - Al-Gurairy, Ahmad; Al-Saad, Furqan (Al-Adab Journal, 2024)
It seems that the blue heavenly stone known as lapis lazuli has been known to the peoples of the ancient world, since the fifth millennium BC, and it quickly gained sanctity in the cultures of those peoples, because of its blue color, which is similar to the color of the sky. The scarcity of this semi-precious metamorphic stone is due to the processes of its formation in nature as a result of magmatic contact with carbonate rocks (limestone or dolomite) and the scarcity of its production in nature due to the great complexity of the processes of its existence. In addition, the aura of sanctity that surrounded it in ancient civilizations made it more expensive than other precious metals such as gold. This prompted its trade routes to grow and develop rapidly since the fifth millennium BC to cover most of the ancient world at that time.The Badakhshan mines in Afghanistan emerged as the main and almost the only region in the ancient world for mining and exporting lapis lazuli, and their global importance continued to expand with the continued quality of lapis lazuli stones extracted from their mines, as in the Sar-e-Sang lapis mine. Although there are discoveries of lapis lazuli in the Baikal region and elsewhere, its low quality makes it unable to compete with Afghan lapis lazuli.Land and river transportation operations have been used to transport lapis lazuli since the middle of the fourth millennium BC, and sea transportation entered this field after 3500 BC. In addition, lapis lazuli stones arrived from Afghanistan to ancient Iraq during the Ubaid civilization (4500 - 3500 BC) and have been of great importance in Mesopotamia since that time. The development of lapis lazuli trade routes and the prosperity of its trade with the societies of ancient Iraq, came from its scarcity and the transformation of this scarcity into sanctity after it was used with gold in the creation of statues and figures of the ancient gods for the inhabitants of Mesopotamia.